Response of Seedling Growth of Wheat and Vegetable Crops (Tomato and Faba bean) to water stress - Rehab I. Tajouri; Mariam M. ELmughrbe; Asma S. Asonosi; Kolod A. Omer; Marwa A. Farj (African Journal of Advanced Pure and Applied Sciences, 2024)
One of the main abiotic stressors that contributes to the largest losses in crop production worldwide is water deficit. This study was to determine the extent of plant tolerance from varity plant families, namely wheat (Triticum aestivum L.), Tomato (Solanum lycopersicum L.) and faba bean (Vicia faba L.) to water stress. The results showed there was inhibition in dry weight and length of shoot of wheat plants when the replication was treated with irrigation after eight days, while in the fresh weight of weight the inhibition occurred when irrigation was after two days, four days, six days and eight days, while tomato plants water stress had not any effect on shoots and length of roots that the inhibition was clear for the fresh weight when irrigation was after six and eight days. In the bean plant, the inhibition was clear in the shoot length irrigated after eight days and had no effect on length of roots at all treatments. As for the fresh and dry weight of bean plants the inhibition occurred when irrigated after eight days. In future research, assessing the response of three main crops to water stress by studying physiological and biochemical traits is very important as they contribute to specify a biotic tolerance range.